Telecentric stereo 3D imaging with isotropic micrometer resolution bridges macro- and microscale in small Lepidopterans - Andreas Walter Stark; Adeoluwa Osadare; Matthew Guo; Gregor Joerg Gentsch; Dennis Boettger; Gunnar Brehm; Christian Franke (Scientific Reports)
Abstract We present a straightforward, application-driven telecentric stereo 3D-measurement system for high-precision measurements, designed for applications ranging from industrial quality control to biological research including scanning of Lepidoptera moths. Utilizing a dual-camera setup with telecentric lenses and structured illumination, our system achieves lateral resolution of 8.0 $$\upmu$$ m and axial resolution of 4.46 $$\upmu$$ m in a measurement volume of 11 mm $$× 11$$ mm $$× 6$$ mm. We address challenges typically encountered when using standard libraries like OpenCV, e.g. in extrinsic parameter estimation using a dedicated calibration method that corrects for a potential model mismatch due to telecentricity. Our approach adapts existing methods, such as telecentric stereo vision and structured illumination, into an optimized, user-friendly system tailored for life science research, enabling detailed 3D-reconstructions of scattering objects, such as small moths, with isotropic micrometer accuracy. This work presents an application-driven approach for biological 3D-metrology by integrating existing technologies (telecentric stereo vision, structured illumination) into a specialized imaging platform suitable for non-invasive morphological studies. Unlike conventional CT or microscopic approaches, our method provides a balance of precision, scalability, and practical usability for non-expert users with the aim to study developmental changes in species under varying environmental conditions, while also methodically bridging the gap between macroscopic and microscopic resolution in biological imaging.